LA EXHIBICIÓN CINEMATOGRÁFICA EN LA CIUDAD DE MURCIA (1896-1996) - Cerón Gómez, Juan Francisco (Imafronte, 1995)
The first film projections in the region took place in the city of Murcia during the September fair of 1896. Cinema became the predominant form of mass entertainment in the 1920s, a time when the historic coliseums of the city were built and the important Iniesta Company was founded. However, the end of the 1920s was marked by a traumatic revolution: the arrival of sound. Cinema projections reached their peak of popularity between the end of the Civil War and the 1960s. It was then that a crisis began, which became worse in the following decade and led to the closure of dozens of auditoriums in the region. Since 1991, a feeble recovery has been noted.